INTERNAL STRUCTURES OF FAULT ZONES IN THE PRIOLKHONIE AND EVOLUTION OF THE STATE OF STRESSES OF THE UPPER CRUST OF THE BAIKAL RIFT - Alexander V. Cheremnykh (Геодинамика и тектонофизика)
The Priolkhonie is a tectonic block located in the central part of the Baikalsky Ridge; it was shifted in the Cenozoic, yet remains above the water level of Lake Baikal. In view of its unique positioning and abundant rock outcropped sites, especially at shorelines, we conducted studies of internal structures of the main fault zones and reconstructed the states of stresses associated with formation of such zones.The studies were conducted along the profile which goes across the Priolkhonie, from the Primorsky Ridge near the Sarma River to the Tutai Bay in the Olkhonskie Vorota Strait (Fig. 1). Detailed cross-sections are constructed to characterize the internal structures of the fault zones striking of the NE-strike, that are located in highly outcropped sites at the shorelines of the Mukhor, Kurkut and other bays.The state of stresses in the fault zones and their vicinities are studied (Fig. 2, 3) by the structural paragenesis analysis of the second-rank ruptures and fracturing nearby the fault planes [Seminsky, Burzunova, 2007]. As possible, the obtained results are checked by the kinematic method which provides for reconstruction of the main axes of normal stresses [Parfenov, 1984].Most of the fault zones are complicated in structure (Fig. 4–7): the fault is typically represented by alternating areas, wherein tectonites of the main fault are developed, and areas of high fracturing at the periphery of the fault zone. With this approach, the fault zone’s boundaries are defined by quantitative indicators of tectonic fracturing, being abundantly manifested in the rocks.Our solutions give evidence that extension (Fig. 8) and shear fractures are abundant in the area under study, while fractures caused by compression are revealed quite rarely. The faults of the above mentioned morpho-genetic types have been revealed in the studied outcrops in the following ratio: 55 %, 27 %, 10 %, and 8 %. Our study gives grounds to conclude that the state of stresses of the upper crust in this territory developed from compression, via shear, to extension. It is also evidenced that strike-slip faults with the left-lateral component and normal faults developed in the Cenozoic.